Intention to buy Halal food product from Non-Muslim manufacturer among Muslims in Selangor / Nazatul Suzana Mohd Fauzi - Mohd Fauzi, Nazatul Suzana (Faculty of Business and Management, 2019)
This study aims to investigate the determinant factors that Muslim consumers may consider in buying Halal food product from Non-Muslim manufacturer where a majority of Muslim consumers have negative perception, still refuse and unconfident to buy those products. There are three determinant factors proposed in this study which is Halal awareness, Islamic brand and product ingredient. Hence, a survey of 278 Muslim consumers around Majlis Perbandaran Kajang company in Selangor was collected to be analyzed. The measuring items for the survey are reliable and valid as its value of Cronbach’s Alpha are bigger than 0.700 in values. Multiple Linear Regression and ANOVA Test was conducted to find out the relationship of the variables as well as the hypothesis suggested and find the answers for all the research questions. The results showed that Halal awareness and product ingredient are positively influenced intention to buy Halal food product from Non-Muslim manufacturer among Muslims in Selangor. It is expected that the findings of the study will beneficial for the Non-Muslim manufacturers to develop the best strategy in winning the heart of Muslim consumers as well as increase Muslim confidence and trust of Non- Muslim Halal food product.